La vulnérabilité de l’université face aux politiques gouvernementales et la coopération internationale nord-sud - Barot, Elisabeth (Canadian Journal of Higher Education, 1991)
This article attempts to examine cooperation between universities in the Northern and Southern hemispheres in the context of the current economic and geopolitical climate. Historical analysis of the nature of the relationship between Canadian universities and their infrastructures reveals the degree to which universities depend on government policies. Given the economic climate of the 1990's, Third World universities find themselves under international as well as national pressure. Mechanisms of international cooperation between universities are analyzed with regard to the role they play in encouraging North-South solidarity at a time when everything seems geared to competition. In conclusion, certain ethical principles are underlined and proposed as a framework within which Canadian universities seem ready to play a role in international North-South cooperation between universities.